Missä asuvat Levin ja Rukan mökkirakennusten omistajat? Maantieteellisestä jakautumisesta etäisyysmalleihin - Kauppila, Pekka (Suomen matkailututkimuksen seura ry, 2008)
Where do the cottage owners of Levi and Ruka live? Geographical distribution and distance models Second home tourism is focused mainly in the hinterland of population centres due to the short distance between the permanent residence of second home owners and second homes. Actually, one of the most important factors for the site selection of a second home is the space-time dimension. The aim of the study is to examine the municipalities of residence of the cottage owners of two large resorts, Levi and Ruka, in Northern Finland. After analysing the geographical distribution of the owners with maps and diagrams, distance models for the resorts are presented. According to the models the resorts have three zones – day trip, weekend and vacation – and each of them has their own characteristics. The investigation underpins the previous study results: in spite of a remote location, an amenity landscape, like a resort, attracts a signifi cant amount of cottages, and many of the cottage owners have their permanent residence outside the weekend zone. Second home tourism is focused mainly in the hinterland of population centres due to the short distance between the permanent residence of second home owners and second homes. Actually, one of the most important factors for the site selection of a second home is the space-time dimension. The aim of the study is to examine the municipalities of residence of the cottage owners of two large resorts, Levi and Ruka, in Northern Finland. After analysing the geographical distribution of the owners with maps and diagrams, distance models for the resorts are presented. According to the models the resorts have three zones – day trip, weekend and vacation – and each of them has their own characteristics. The investigation underpins the previous study results: in spite of a remote location, an amenity landscape, like a resort, attracts a signifi cant amount of cottages, and many of the cottage owners have their permanent residence outside the weekend zone.